JSPS-9 Microbiologial Quality of Chicken Carcasses in Bogor Indonesia Based on Campylobater sp. and Salmonella sp. Counts - Herwin Pisestyani; Elisabet Tangkonda; Maya Shofa; Surachmi Setyaninigsih; Denny Widaya Lukman; Bambang Pontjo Priosoeryanto; Naoaki Misawa (Hemera Zoa, 2018)
Unhygienic handling chicken carcasses during slaughtering until selling to costumers can lead to contamination by pathogenic bacteria such as Campylobacter sp., and Salmonella sp. entering human’s body can cause foodborne diseaseThe aims of this study were to detect contamination and enumuration of Campylobacter sp, and Salmonella sp. in chicken carcasses from poultry slauhterhouses and markets in Bogor Indonesia.